Arhuaco ancestral knowledge as a technopedagogical strategy for the development of environmental awareness in fourth-grade students of Colegio La Sagrada Familia - Ariza Córdoba, Keyla Vanessa; Oñate Quiroz, María Claris; Hernández Lazo, Rolando (Revista UNIMAR, 2023)
The objective of this research was to implement a techno-pedagogical strategy based on the ancestral knowledge of the Arhuaca indigenous community, to develop environmental awareness in fourth-grade students of the primary school ‘La Sagrada Familia’ in the city of Valledupar. The research had a qualitative approach and a socio-critical paradigm that allowed identifying the potential for change in the way students perceived and related to nature. The action research method was applied, which was developed in three phases: deconstruction, reconstruction, and evaluation. The work unit consisted of 15 students. The results indicated that there was a significant change in the development of environmental awareness in each of its dimensions. It was concluded that, although the implemented techno-pedagogical strategy provided a great contribution to the integral formation of the student, it is recommended to link technological tools and ancestral knowledge to pedagogical projects, as a contribution to educational processes.